A Unique ALCAPA Variant in a Neonate1. Issue 3 (11th March 2013) - Smith, Deane E.; Adams, Robert; Argilla, Michael; Phoon, Colin K.L.; Chun, Anne J.L.; Bendel, Marci; Mosca, Ralph S.
Abstract Anomalous left coronary artery from the pulmonary artery (ALCAPA) is a rare congenital anomaly present in approximately one in 300, 000 live births. Here, we present a unique ALCAPA variant identified in a neonate. The left anterior descending artery originated posterolaterally on the main pulmonary artery, and the circumflex originated separately from the distal right pulmonary artery. doi: 10.1111/jocs.12079 (J Card Surg 2013;28:306–308)